Combinations of steam-flaked corn, dry-rolled corn, and dried distillers grains yield beef with similar yet subtle changes in sensory traits - Black, P.L.; Parsons, G.L.; Shelor, M.K.; Karges, K.K.; Gibson, M.L.; Dikeman, Michael E.; Drouillard, James S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
Rapid expansion of fuel ethanol production has made available abundant supplies of distillers grains with solubles, which are well-suited as a substitute for cereal grains in finishing cattle diets. Several recently reported experiments have revealed that feeding distillers grains may have adverse effects on carcass value as a result of the tendency to produce carcasses with lower quality grades and/or higher yield grades. The effects on quality grade have been most evident in flaked-grain diets, but effects on yield grade are more or less independent of the type of grain fed. In Kansas, two common methods for processing grains are steam flaking and dry rolling. Thus, feeding cattle distillers grains with different grain processing types is an important consideration for feedlots. Our experiment was designed to evaluate meat quality and composition in heifers fed flakedcorn diets containing dry-rolled corn and/or dried corn distillers grains.
Keywords: Beef; Cattle; Distillers grains